ANALISIS PERLINDUNGAN HUKUM TERHADAP PENCIPTA TARIAN YANG CIPTAANNYA DIUNGGAH DI YOUTUBE OLEH PIHAK LAIN TANPA SEIZIN DARI PENCIPTA TARIAN BERDASARKAN UNDANG – UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Alfandi Alfandi; Christine S.T. Kansil (Jurnal Hukum Adigama, 2021)
A dance is the result of someone's creativity or idea which when the idea is channeled into a dance or choreography, the idea will automatically get the status of a work, and the choreographer who created the choreography will automatically get exclusive rights to the object and will referred to as the creator who has the copyright, but the copyright law has not regulated the Cover which is then uploaded on YouTube which puts the position of this perpetrator in the gray zone (Grey Area) which means that this action clearly violates the protection of the creator as the right holder. copyright, but the act cannot be legalized according to the applicable laws and regulations. With the development of the times, the recognition of copyright protection is also expanding, in addition to registering, creators can also take advantage of the facilities provided by an institution known as creative common, which in addition to providing protection, it also allows the work to be distributed by other parties, so that creators can be more easily recognized by many people and their work is appreciated by many people.